Hemithyroidectomy versus total thyroidectomy for well differentiated T1–2 N0 thyroid cancer: systematic review and meta‐analysis. Issue 6 (6th October 2020) - Rodriguez Schaap, P. M.; Botti, M.; Otten, R. H. J.; Dreijerink, K. M. A.; Nieveen van Dijkum, E. J. M.; Bonjer, H. J.; Engelsman, A. F.; Dickhoff, C.
Abstract : Background: Evidence for limiting the extent of surgery in patients with low‐risk thyroid cancer is lacking. Methods: A systematic search was performed according to the PRISMA and MOOSE guidelines to assess the effect of total thyroidectomy (TT) with or without radioactive iodine (RAI) treatment versus hemithyroidectomy (HT) on recurrence and overall mortality in patients with differentiated (papillary or follicular) T1–2 N0 thyroid cancer. PubMed, Embase and Cochrane databases were searched, and two authors independently assessed the articles. Results: A total of ten eligible articles were identified. All were observational cohort series, representing a total of 23 134 patients, of which 17 699 were available for meta‐analysis. Six studies included patients who had TT followed by RAI treatment. The pooled recurrence rate after TT ± RAI and HT was 2·3 and 2·8 per cent respectively (odds ratio (OR) 1·12, 95 per cent c.i. 0·82 to 1·53; P = 0·48). The pooled 20‐year overall survival rate after TT ± RAI was 96·8 per cent, compared with 97·4 per cent for HT (OR 1·30, 0·71 to 2·37; P = 0·40). Overall, higher complication rates were found in the TT ± RAI group. Conclusion: Recurrence rates after HT for treatment of well differentiated T1–2 N0 thyroid cancer were similar to those after TT ± RAI, with a lower incidence of treatment‐related complications. Abstract : This systematic review and meta‐analysis showed similar recurrence rates after hemithyroidectomy for selected patients with well differentiated T1–2 N0 thyroid cancer to those in patients who had a total thyroidectomy with or without radioactive iodine treatment, with lower reported rates of treatment‐related complications. Supports conservative surgery Abstract : Antecedentes: No hay evidencia para limitar la extensión de la cirugía en pacientes con cáncer de tiroides de bajo riesgo. Métodos: Se realizó una búsqueda sistemática siguiendo las recomendaciones PRISMA ( Preferred Reporting Items for Systematic Reviews and Meta‐analysis ) y MOOSE ( Meta‐analysis of Observational Studies in Epidemiology ) para evaluar el efecto de la tiroidectomía total (TT) +/− yodo radioactivo ( radioactive iodine treatment, RAI) versus hemitiroidectomía (HT) en la recidiva y en la mortalidad global en el cáncer de tiroides diferenciado (papilar/folicular) T1‐T2N0. Se realizaron búsquedas en las bases de datos PubMed, Embase y Cochrane, y dos autores evaluaron los artículos de forma independiente. Resultados: Se identificaron un total de 10 artículos de interés. Todos ellos eran estudios de cohortes observacionales, con un total de 23.134 pacientes, de los cuales 17.699 se incluyeron en el metaanálisis. En seis estudios, los pacientes fueron tratados mediante TT seguida de RAI. Las tasas agrupadas de recidiva tras TT +/− RAI y HT fueron 2, 3% and 2, 8%, respectivamente (razón de oportunidades, odds ratio, OR = 1, 12, i.c. del 95% 0, 82‐1, 54, P = 0.48). La supervivencia global a 20 años de TT +/− RAI fue del 96, 8% en comparación con el 97, 4% para la HT (OR = 1, 30, i.c. del 95% 0, 71‐2, 37, P = 0, 40). Globalmente, se observaron más complicaciones en el grupo de TT +/− RAI. Conclusión: Esta revisión sistemática con metaanálisis demuestra tasas de recidiva similares tras una HT para el tratamiento del cáncer de tiroides T1‐2N0 bien diferenciado en comparación con TT +/− RAI, con una menor incidencia de complicaciones relacionadas con el tratamiento.